Knowledge and Practices Regarding Childbirth among the Rural Mothers: Attending Upazilla Health Complex (UHC), Anowara, Chattogram, Bangladesh - Begum, Kamrun Nesa; Akter, Syeda Yeasmin; Barua, Srabani; Rosy, Monowara Sultana (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Traditionally delivery at home is the most common practice in Bangladesh. Births delivered at home are more likely to be delivered without medical assistance. Whereas births delivered at a health facility are delivered by skilled birth attendants. The level of care a woman received during the birth of her child has important health consequences for both mother and child. Besides, appropriate antenatal care (ANC) has long been considered a crucial component of the continuum of care during pregnancy with the potential to contribute to the survival of women and newborns. The study aims to analyse the knowledge and practices regarding childbirth among the rural mothers of Bangladesh. It is a cross-sectional study carried out in the outpatient Department of Anowara Upazilla Health Complex, Chattogram, Bangladesh from September 2019 to February 2020. In this study, more than 90% patient aged 15-25 years, 68% housewife, 73% patient has TT coverage but 47% do not know about ANC. UHC is the most common place to take ANC, 62% delivery was conducted at home and 38% was institutional. Among all these cases 45% birth was attended by skilled birth attendant (SBA) and 38% by untrained dai. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 120-125